Analisis Transaksi Online Terhadap Kepercayaan Pembelian Dan Kepuasan E-Commerce Grab Indonesia Di Kota Pekanbaru - Siti Aisyah; Zulkarnain; Kasman Arifin (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2020)
Business opportunities for buying and selling that previously could only be done in supermarkets, malls, shops, or markets called offline businesses can now be done using online media by creating sales websites or by using social networking media. This study aims to determine the Analysis of Online Transactions Against Purchase Trust and Grab E-commerce Satisfaction in Pekanbaru City. The population taken in this study is from the Districts in Pekanbaru City, namely the Districts of Tampan, Marpoyan Damai, Pekanbaru City and Bukit Raya, with a total of 548,730 inhabitants. The method used in this study uses quantitative methods with causal and descriptive research designs. And testing the hypothesis in this study using Structural Equation Modeling (SEM) analysis. Data collection techniques are done by interview and questionnaire. The results of this study indicate that the coefficient of determination obtained value of 0.760. This means that 76% of purchasing confidence variables are obtained from online transactions consisting of security, privacy, brand name, word of mouth, good experience and quality of information. The e-commerce satisfaction variable was 0.815. This means that 81.5% of e-commerce satisfaction variables are approved by online transactions and purchase confidence. While the partial test relationship of H1, H2, H5, H6, H7, H8, H8, H10, H11, H12, H13, have a positive and significant effect. While H3, H4 and H10 have a positive and not significant effect